A cost-effectiveness analysis of alternative survey methods used for the monitoring of marine recreational fishing in France. (15th March 2017) - Bellanger, Manuel; Levrel, Harold
Abstract: The growth of marine recreational activities raises the issues of the current lack of knowledge on these activities and the information required to assess their potential impacts. Indeed, the monitoring of unrecorded activities is a great challenge, especially when basic information, such as the size of the population practicing the different activities, is unknown. In this paper, the experience of the monitoring of marine recreational fishing was used to carry out a diagnosis study to assess the cost-effectiveness of survey methods used in France between 2004 and 2012. Costs of alternative surveys were balanced with data quality, and particular attention was paid to potential biases. Results showed that the involvement of citizens through diary surveys could be a cost-effective option when the recruitment of participants complied with randomness and representativeness requirements. The outcomes of this study provide useful insights to help managers and decision makers implement monitoring schemes in similar contexts. Highlights: Precise costs of the different types of survey are provided and compared. Accuracy of effort and catch rate estimates is poor for most surveys. Diary surveys with involvement of citizens were found particularly cost-effective. Recruitment of participants must ensure randomness and representativeness. Findings are relevant for future monitoring schemes in a variety of contexts.